Anemia among adolescents in urban field practice area of Rajarajeswari Medical College, Bangalore - M.N. Damayanthi; P. Seema; Jayanth Kumar (Al Ameen Medical College, 2015)
Background: Anemia is a public health problem in developing countries which affects both male and female adolescents.50% of all anemia's is attributable to iron deficiency. Methodology: A Cross-sectional study done in urban field practice area of RRMCH over a period of three months was conducted on 220 adolescents aged between 10-19yrs (both male and female). Data was collected using a semi-structured questionnaire with emphasis on variables like socio-demographic profile, history of passing worms in stools and menstrual history for females. Hemoglobin was estimated by using Sahli's hemoglobinometer. Data analysis: SPSS V 20. Results: Occurrence of anemia in our study was 47.7% i.e.; (105 of 220) of which, 61(58.1%) were males and 44(41.9%) of them were female adolescents. Majority of the adolescents had moderate anemia (60%), mild anemia (38.1%) and severe anemia (01.9%).Some of the factors contributing to anemia were menorrhagia, history of passing of worms in the stools which were statistically significant. Conclusion: The study highlights the prevalence of anemia not only among the adolescent girls, but the risk is evenly distributed for the boys too. There is a need to reach this adolescent population through school approaches through nutrition education and distribution of iron and folic acid supplementation.